Metode Istinbath Hukum calam Pandangan Ulama Hanafiah - Abshor, M. Ulil (LP2M Institut Agama Islam Al-Qur'an Al-Ittifaqiah Indralaya, 2022)
In doing legal decide and efforts made by Law Scholarships (read: Mujtahid) to understand text, basically not only refers to the form of pronunciation with a variety of pronunciation arrangement or it can be called the appropriate meaning of what is written, but the implicit meaning is like the sign of the meaning contained in the pronunciation and with it. In the science of Ushul Fiqih can be affirmed through Dalalah is a purpose to a certain meaning. Because Dalalah is a relationship between al-Dal and al-Madlul Al-Dal is lafazh while Al-Madlul is linguistik meaning (lughowi) Suppose al-Dal recites